Persistent hyperthyroidism and de novo Graves' ophthalmopathy after total thyroidectomy. (13th October 2017) - Tay, Wei Lin; Loh, Wann Jia; Lee, Lianne Ai Ling; Chng, Chiaw Ling
Summary: We report a patient with Graves' disease who remained persistently hyperthyroid after a total thyroidectomy and also developed de novo Graves' ophthalmopathy 5 months after surgery. She was subsequently found to have a mature cystic teratoma containing struma ovarii after undergoing a total hysterectomy and salpingo-oophorectomy for an incidental ovarian lesion. Learning points: It is important to investigate for other causes of primary hyperthyroidism when thyrotoxicosis persists after total thyroidectomy. TSH receptor antibody may persist after total thyroidectomy and may potentially contribute to the development of de novo Graves' ophthalmopathy.